Case Report: Leaflet Thrombosis After Transcatheter Aortic Valve Replacement With Worsening Heart Failure—A Successful Resolution Using Non-vitamin K Antagonist Oral Anti-coagulant - Liang, Kae-Woei; Yu, Chu-Leng; Lin, Wei-Wen; Lee, Wen-Lieng (Frontiers in Cardiovascular Medicine, 2021)
Background: Transcatheter aortic valve replacement (TAVR) is indicated for treating symptomatic severe aortic valve stenosis (AS) with intermediate to high surgical risks. Few reports are available on managing leaflet thrombosis after TAVR with worsening heart failure. Case summary: A 77-year-old man with severe AS and coronary artery disease (CAD) received a successful transcatheter aortic valve replacement (TAVR) with Edwards Sapien 3 valve. A year later, he developed worsening heart failure with pulmonary edema, new onset atrial fibrillation (Af), an increase in mean trans-aortic valve pressure gradient to 48 mmHg, worsening mitral regurgitation (MR) and pulmonary hypertension (PH). His response to intravenous diuretics and inotropics treatments was poor. Multi-slice computed tomography (MDCT) revealed hypo-attenuated thrombus and thickened trans-catheter heart valve leaflets. A non-vitamin K antagonist oral anti-coagulant (NOAC) was added to treat the new onset Af and leaflet thrombosis on top of the con-current single antiplatelet for CAD. A series of follow-up echocardiograms showed a progressive decrease in trans-aortic valve pressure gradient to 17 mmHg and reductions in MR and PH. Three months after the NOAC treatment, MDCT revealed the resolution of hypo-attenuated thrombus and thickened leaflets. Symptoms of heart failure also improved gradually. Discussion: Worsening heart failure or an increase in trans-aortic valve pressure gradient after TAVR warranted further MDCT studies. Leaflet thrombosis can be resolved after using NOAC as in our present case.